2011
DOI: 10.1093/czoolo/57.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in the paddyfield warbler (Acrocephalus agricola Jerd.)

Abstract: Population genetic structure was studied in paddyfield warblers Acrocephalus agricola breeding in NE Bulgaria, SE Russia and S Kazakhstan. We were particularly interested in the degree of genetic differentiation and gene flow of the Bulgarian population due to its geographical isolation, recent origin and unique migratory strategy. Analyses of mitochondrial DNA (mtDNA) showed that there was no divergence between Bulgarian and Russian populations (FST = 0.007), whereas those in Kazakhstan differed significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…This was indicated by the low effective allele numbers, which were around half of the allele numbers per locus, and by the low expected heterozygosity and allelic richness. Importantly, our H E estimates of 0.44-0.48 are similar to values recovered in endangered bird species (Evans & Sheldon 2008, Vitorino et al 2019) and, on average, appear lower than H E values observed in other studied Acrocephalus species (Hansson & Richardson 2005, Kralj et al 2010, Proch azka et al 2011, Zehtindjiev et al 2011, Ceresa et al 2015.…”
Section: Low Genetic Diversitysupporting
confidence: 67%
“…This was indicated by the low effective allele numbers, which were around half of the allele numbers per locus, and by the low expected heterozygosity and allelic richness. Importantly, our H E estimates of 0.44-0.48 are similar to values recovered in endangered bird species (Evans & Sheldon 2008, Vitorino et al 2019) and, on average, appear lower than H E values observed in other studied Acrocephalus species (Hansson & Richardson 2005, Kralj et al 2010, Proch azka et al 2011, Zehtindjiev et al 2011, Ceresa et al 2015.…”
Section: Low Genetic Diversitysupporting
confidence: 67%
“…Avian malaria and related haemosporidian parasites (e.g. Plasmodium and Haemoproteus ) have been recorded in many bird species worldwide (Valkiūnas et al 2006) and parasitized individuals frequently carry simultaneous infections by more than one parasite species or strain (mixed or co‐infections) (Valkiūnas et al 2003, Palinauskas et al 2005, Krizănauskiené et al 2010, Loiseau et al 2010, Asghar et al 2011, Zehtindjiev et al 2011, Piersma and van der Velde 2012). However, the effects of such co‐infections of avian malaria parasites are largely unknown.…”
mentioning
confidence: 99%
“…This situation is not unique to the RBS, but actually a common phylogeographic status for many bird species currently distributed in Eurasia. Genetic admixture has been previously shown to characterize the Hoopoe (Upupa epops) population [54], the White-winged Snowfinch (Montifringila nivalis) [55], the Common Sandpiper (Actitis hypoleucos) [56], the Marsh Warbler (Acrocephalus palustris) [57], the Paddyfield Warbler (Acrocephalus agricola) [58], the Eurasian Reed Warbler (Acrocephalus scirpaceus) [59], the Western Capercaillie (Tetrao urogallus) [60], the Hazel Grouse (Tetrastes bonasia) [61], the Eurasian Blackcap (Sylvia atricapilla) [62], the European Bee-eater (Merops apiaster) [63], and the Eurasian Jay (Garrulus glandarius) [64], to name just a few. For the RBS, this genetic background is a clear result of Pleistocene climatic history (see next chapter), with different lineages coming together into refugia and, possibly, even bird movements between different refugia.…”
Section: Behind the Mask: Genetic Panmixiamentioning
confidence: 99%